The philosophy, theology, and rhetoric of Marius Victorinus - Cooper, Stephen A.; Němec, Václav, 1969- (Writings from the Greco-Roman world supplement series ;, 2022)
This collection of essays is devoted to the rhetoric, Neoplatonic philosophy, and Christian theology of Marius Victorinus, a mid-fourth-century professor of rhetoric and philosopher who converted to Christianity late in life. Scholars from eight different countries, some of whom have not previously published in English, reflect on debates about his writings and theological development. These topics include Victorinus's deployment of philosophical sources for trinitarian theology, possible connections in his work to Origen, Augustine, Plotinus, Porphyry, and Gnosticism, as well as his contributions to Latin rhetoric and dialectic. Contributors include Jan Dominik Bogataj, Michael Chase, Nello Cipriani, Stephen A. Cooper, Volker Henning Drecoll, Lenka Karfíková, Josef Lössl, Václav Němec, Thomas Riesenweber, Guadalupe Lopetegui Semperena, Miran Špelič, Chiara O. Tommasi, John D. Turner, and Florian Zacher. The chapters in this volume are of great interest to students of late antique philosophy, Christian theology, and Latin rhetoric.